DIGITAL TRANSFORMATIONS OF THE LIFE INSURANCE INDUSTRY - Sh.A.Zakirkhodzhayeva, (TADQIQOTLAR, 2026)
ANNOTATION: the topic is considered relevant, in which the implementation of the types of life insurance in Uzbekistan is analyzed and the need to digitize the process of implementing the types of life insurance.